"I Know It Seems Weird, but Don't Tell Anybody": Further Exploring Tellability in Untold Stories of Caregiving. Issue 4 (8th August 2022) - Jackl, Jennifer A.
Abstract : Narrative tellability is a guiding principle that enables scholars to understand how, when, and to whom a story is (not) told. The current study was done while considering ideas of the theory of communication privacy management to further understand narrative tellability within the context of unpaid, informal care. Unpaid, informal caregivers are at a challenging intersection of privacy management, as they navigate their own, as well as their loved one's, private information. From the qualitative, inductive analysis of 20 narratives, characteristics of tellability emerged as: Story would do Undesirable Identity Work, Story would Produce Negative Sanctions, and Story would Negatively Impact Relationship(s). I conclude with a discussion of conceptual and practical implications of viewing narrative tellability through the lens of privacy management.